KOTORAN TERNAK SEBAGAI INOKULUM PADA PENGOLAHAN AIR LIMBAH PABRIK GULA SECARA BIOLOGI-AEROB - Hendro M Santoso; Yahya Kurniawan (Research Center for Chemistry - LIPI, 1999)
A study on the treatment of Sugar Factory wasted water by using biological aerobic process was carried out at a laboratory sacle. Cow dung and chicken dung were used as inoculum to raduce the organic compounds is waste water. The levels of inoculum concentration used were 5; 10; 15; 20; and 25 per cent. The experiment was conducted bt a one way completely randomize design. The treatment process was followed by observing the changes in the BOD and COD parameters. The results showed that the chicken dung inculum reduce COD content up to 73-76 per cent and BOD content up to 81-86 per cent. The cow dung inculum reduced COD and BOD contents up to 97-92 percent and up to 65-95 per cent respectively.